Thirteen-week nose-only inhalation exposures of propylene glycol aerosols in Sprague Dawley rats with a lung systems toxicology analysis. (12th July 2021) - Langston, T; Randazzo, J; Kogel, U; Hoeng, J; Martin, F; Titz, B; Guedj, E; Schneider, T; Prabhakar, B; Zhang, J; Oldham, M; Lee, KM
The objectives of this study were to increase PG exposure above concentrations tested by Suber et al. and use systems toxicology analysis of lung tissue to understand molecular events. Sprague Dawley rats were exposed to filtered air (sham), propylene glycol/water (PG/W; 90:10) or a propylene glycol/vegetable glycerin/water (PG/VG/W; 50:40:10) reference. The reference group was added at the high dose to observe any changes that might be associated with a carrier more in line with e-vapor products. Macroscopic examinations and terminal organ weights revealed no observations associated with exposure to PG/W or reference. Food consumption and body weights were unaffected by PG/W or reference when compared to sham. No exposure related alterations were observed in serum chemistry, hematology, coagulation, urinalysis or BALF cytology and clinical chemistry. Although clinical observations of dried red material around the nose in the high dose PG/W group were reported, histopathology showed no nasal hemorrhaging which was previously reported by Suber et al. Non-adverse PG/W and reference related findings of minimal mucous cell hyperplasia were noted in nasal cavity section II. No other exposure-related findings were noted in the primary or recovery necropsies. A systems toxicology analysis on lung tissue showed no statistically significant differentially expressed transcripts or proteins compared to the sham group. The endpoints measured from the PG/W high dose group did not differ significantly from those in the more common carrier PG/VG/W. As anticipated, exposure to PG aerosols was slightly irritating but well tolerated. Accordingly, the highest PG exposure (5 mg/L, 6 hrs/day) was regarded as the NOAEC, corresponding to a PG delivered dose of 1, 152 mg/kg/day in rats.